Yield and Input Use Efficiency of Maize (Zea mays L.) as Influenced by Crop Residue Mulch, Irrigation and Nitrogen Management - R. Singh, S. Pradhan; S.P. Datta, Sumanta Chatterjee, K.K. Bandyopadhyay (Journal of the Indian Society of Soil Science, 2017)
Field experiments were conducted in a sandy loam soil at the research farm of the Indian Agricultural Research Institute (IARI), New Delhi during the kharif season of 2012 and 2013 with the objective to study the effect of crop residue mulch, irrigation and nitrogen (N) on soil water dynamics, growth, yield, water and N use efficiency of maize. Maize (cv. HQPM 1) was grown in a split-split plot design with two levels of irrigation, two levels of mulch and three levels of N. The grain yield of maize increased significantly by 31 per cent under irrigated condition than that of rainfed condition in the year 2012. Application of crop residue mulch increased the grain yield of maize significantly by 11.5 and 28.4 per cent compared to no-mulch treatment in 2012 and 2013, respectively. Application of N significantly increased the grain yield of maize over the control. However, there was no significant difference between 75 kg and 150 kg N ha-1 with respect to grain and biomass yield of maize. The water use efficiency of maize increased significantly by 12.6 and 36 per cent in 2012 and 2013, respectively due to crop residue mulch. The apparent N recovery and agronomic N use efficiency increased significantly but physiological N use efficiency decreased under mulching. So, maize may be grown with 75 kg N ha-1 and wheat residue mulch @ 10 t ha-1 to achieve higher yield, water use efficiency and N use efficiency in Upper-Indo-Gangetic Plain region.